2015
DOI: 10.1159/000365810
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Aneuploidy Detection of Chromosomes 13, 18, 21, X and Y Using Quantitative Fluorescent Polymerase Chain Reaction with Few Microdissected Fetal Cells

Abstract: Objectives: Analysis of DNA from small numbers of cells, such as fetal cells in maternal blood, is a major limiting factor for their use in clinical applications. Traditional methods of single-cells whole genome amplification (SCs-WGA) and accurate analysis have been challenging to date. Our purpose was to assess the feasibility of using a few fetal cells to determine fetal sex and major chromosomal abnormalities by quantitative fluorescent polymerase chain reaction (QF-PCR). Methods: Cultured cells from 26 am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…WGA is an essential step to provide the sufficient amount of DNA for the downstream analysis. A previous study has shown that WGA performed on few cultured fetal cells from amniotic fluid did have a sufficient genome coverage to provide accurate detection of major fetal chromosome abnormalities . Some of the authors of this article have previously shown that WGA on single cells could be used to detect copy number changes larger than 1 MB using array CGH …”
Section: Discussionmentioning
confidence: 90%
“…WGA is an essential step to provide the sufficient amount of DNA for the downstream analysis. A previous study has shown that WGA performed on few cultured fetal cells from amniotic fluid did have a sufficient genome coverage to provide accurate detection of major fetal chromosome abnormalities . Some of the authors of this article have previously shown that WGA on single cells could be used to detect copy number changes larger than 1 MB using array CGH …”
Section: Discussionmentioning
confidence: 90%
“…The capacity to assess genomic copy number from a single cell by array comparative genomic hybridization (CGH) presents an important advance for both basic research and clinical diagnostics, with relevance to multiple fields including cancer genetics, preimplantation genetic diagnosis (PGD) and prenatal non‐invasive fetal genome analysis. Recent studies have shown that genome‐wide copy number assessment of single cells can be accomplished using whole‐genome amplification (WGA), which can generate sufficient quantities of DNA for array CGH . At the present time, there is strong interest in developing methods for enriching fetal cells from the maternal circulation to a point where they could be subjected to WGA, as a step towards cell‐based non‐invasive prenatal diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The loci D13S317 (at 13q31.1) and D13S634 (at 13q14.3) were used to assess chromosome 13. The loci Amelogenin (located at Xp22.3), DXS8106 (at Xq27.3) and DXS7132 (at Xq11.2) were used to assess the sex chromosomes (16,17). Primer sequences are presented in Table I.…”
Section: Methodsmentioning
confidence: 99%